Workshop on Assistance for Subject Teachers for Science Subject Develop A Diagnostic Assessment - RAHMATIA THAHIR; MUHAMMAD WAJDI; NURDIYANTI; RIZA SATIVANI; TRY AYU PATMAWATI (International Journal of Multidisciplinary Research and Studies, 2023)
School Indonesia Kuala Lumpur (SIKL) has a strategic role and is at the forefront of educational diplomacy in Malaysia in the context of Indonesian human resource (HR) development based on Pancasila and the 1945 Constitution. Since its founding on July 10 1969, SIKL has consistently taken part in providing education services to the Indonesian community in Malaysia which refers to the basis of national education. The service is carried out to answer and solve the problems faced by the partners of the Kuala Lumpur Indonesian School. The solution offered by the service team to partners to overcome the problems encountered is in the form of a diagnostic assessment development workshop. The method of carrying out activities is to use the Technology, Paedagogy, learning model. and Content Knowledge (TPACK) which is the model used in the workshop and continued online. The TPACK model consists of 4 steps, namely: Understanding (P), observation-instruction (O), instruction practice (L), and reflection (R). The result of the activity is an increase in science teachers' knowledge and skills in developing diagnostic assessments such as assessment of learning styles, interests and talents, and learning readiness.